PENINGKATAN HASIL BELAJAR PKn MENGGUNAKAN MODEL NHT DI KELAS IV SEKOLAH DASAR - Muhardi, M.; Salimi, Asmayani; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this study was to improve student learning outcomes in learning civic education using cooperative learning models type numbered head together in class IV State Elementary School 05 Bengkayang Gathering. The research method used is descriptive, a form of classroom action research, the nature of collaborative research. Data collection techniques used in this study are direct observation and document scrutiny. The data collection instruments used were observation sheets in the form of learning planning assessment instruments and assessment instruments for the implementation of learning. The document that is examined is a sheet of students' formative learning outcomes. This research was conducted in three cycles, the results obtained were the ability of researchers to design learning in the first cycle with an average value of 3.17 increasing in the second cycle to 3.48, and the third cycle to 3.83. The ability of teachers to carry out learning in the first cycle was 3.06, the second cycle to be 3.39 in the third cycle was 3.65. Student learning outcomes have increased each cycle after applying the numbered head together model. In the first cycle the average learning outcomes of students were 65.53, in the second cycle it increased to 79.29 and the third cycle became 84.09. The conclusion of this research is that there is an increase in the learning outcomes of citizenship education in the application of the numbered head together model in the fourth grade of the 05 Meeting Elementary School, Bengkayang.Â Keywords: Numbered Head Together, Learning Outcomes, Civic Education.